2014
DOI: 10.1021/ef4021087
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Gaseous Sulfur Species Formation during the Steam Hydrogasification of Coal

Abstract: Steam hydrogasification is the thermochemical conversion of carbonaceous materials into synthesis gas in a steamand hydrogen-rich environment. The formation of gas-phase sulfur species during the pyrolysis and gasification of sulfurcontaining feedstocks, such as coal, presents well-known challenges. Gas-phase sulfur component formation under typical steam hydrogasification conditions was studied experimentally, and the impact of process parameters has been evaluated. The experimental results show that sulfur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, the total amount and rate of H 2 S in the PL system increased significantly compared with that of the P system. The results showed that the introduction of H 2 O promoted the formation of H 2 S, which is consistent with the experimental results. ,,, …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…However, the total amount and rate of H 2 S in the PL system increased significantly compared with that of the P system. The results showed that the introduction of H 2 O promoted the formation of H 2 S, which is consistent with the experimental results. ,,, …”
Section: Resultssupporting
confidence: 90%
“…The results showed that the introduction of H 2 O promoted the formation of H 2 S, which is consistent with the experimental results. 8,13,19,20 3.3. Effect of H 2 O on Chemical Bonds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The H 2 S content remains in the 1000–2000 ppm range during the whole campaign, which is a common order of magnitude for coal gasification. ,, COS measurement could not be performed because the H 2 O peak overlays the expected COS peak, but there are several publications that indicate a low concentration of COS in lignite-derived synthesis gas under reducing atmosphere . Thiophene concentration varied between 10 and 30 ppm, which is rather at the level of biomass gasification than other lignite-derived synthesis gas. , …”
Section: Resultsmentioning
confidence: 99%